2015
DOI: 10.15344/2394-4978/2015/121
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Stimulation at the Jing-Well Points of Meridians

Abstract: Objective: To investigate the efficacy of stimulation at the Jing-Well points of meridians in advanced clinical practice. Methods: Articles including English or Chinese keywords on the Jing-Well points of meridians published between 2001 and August 2012 were sourced from the Cochrane Library, PubMed, and China National Knowledge Infrastructure databases. On the basis of these reports, we explored the modern applications, mechanisms, and efficacy of the Jing-Well points. Results: Thirty-five related studies, pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…According to TCM, K1 (Yongquan), DU26 (Renghong) and DU25 (Suliao) are effective acupoints in retrieving consciousness (15-17). Kidney channel plays an important role in consciousness, particularly K1 (Yongquan) as jing-well point of kidney meridian which can bubble up chi through the channel (20, 21). Therefore, in this study we employed K1 as a common acupoint in conjunction with two other acupoints, DU26 and DU25, separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to TCM, K1 (Yongquan), DU26 (Renghong) and DU25 (Suliao) are effective acupoints in retrieving consciousness (15-17). Kidney channel plays an important role in consciousness, particularly K1 (Yongquan) as jing-well point of kidney meridian which can bubble up chi through the channel (20, 21). Therefore, in this study we employed K1 as a common acupoint in conjunction with two other acupoints, DU26 and DU25, separately.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the stimulation can be applied by electro stimulation, moxibustion or laser. There are some other acupoints with proven effects in resuscitation and consciousness improvement such as PC-9 (Zhong Chong) (15, 21) which would be worth investigating in the recovery setting of anesthesia in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The finding showed that the level of mammary filling, breast milk production, and prolactin level was higher in the group given acupressure on SI1. Electroacupuncture on SI1 is not only able to improve prolactin level but also improves lactation after delivery (Tseng, 2015).…”
Section: Breast Milk Production Of Primiparous Mothers In the Postparmentioning
confidence: 96%
“…In the present study, we adopted a cutting‐edge vascular perfusion microscopic dissection technique to preserve and demonstrate the original subcutaneous structures beneath APs in two fresh adult upper limb specimens. Thirty five‐Shu APs on the forearm were chosen as the target APs because they are better established and more widely used in clinical treatment than others (Cho & Kim, 2021; Tseng et al, 2015). They can be subdivided into Jing (“井”), Ying (“荥”), Shu (“输”), Jing (“经”), and He (“合”) acupoints.…”
Section: Introductionmentioning
confidence: 99%